2006
DOI: 10.1007/s00261-005-0393-6
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder adenoma: report of a case with emphasis on contrast-enhanced US findings

Abstract: There is a marked paucity of contrast-enhanced ultrasound (US) findings of gallbladder disease in the literature, and there is only one previous case of gallbladder adenoma. We report such a case. US showed a 2-cm polypoid lesion at the gallbladder body. Color Doppler US showed the hypervascular nature of the lesion, and contrast-enhanced US revealed the lesion to be homogeneously enhanced, suggesting that the lesion was composed of the same pathology. The lesion was surgically resected, and was found to be an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Although the CEUS study has been used to evaluate acute and chronic gallbladder disease, data about its usefulness in the detection of inflammatory complications of acute cholecystitis are sparse [10,[24][25][26][27][28][29][30]. Few reports focus on the diagnostic aid of a CEUS study in the detection of complicated acute cholecystitis such as gangrenous changes or perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the CEUS study has been used to evaluate acute and chronic gallbladder disease, data about its usefulness in the detection of inflammatory complications of acute cholecystitis are sparse [10,[24][25][26][27][28][29][30]. Few reports focus on the diagnostic aid of a CEUS study in the detection of complicated acute cholecystitis such as gangrenous changes or perforation.…”
Section: Discussionmentioning
confidence: 99%
“…The successful use of CEUS in other organs such as liver, kidney, and pancreas has prompted the use of CEUS in GB [13], [15], [19]. Unfortunately, its usefulness in GB is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Although CEUS has been tentatively used in GB diseases, the role of CEUS in GB is less well recognized and multicenter experience is not available [10], [11], [12], [13], [14], [15], [16]. In this prospective study, the application of GB CEUS in 9 centers was reported with an aim to evaluate the role of CEUS in the differential diagnosis between benign and malignant GB diseases.…”
Section: Introductionmentioning
confidence: 99%
“…mechanical index less than 0.2) has been introduced in the diagnosis of GB diseases in recent years since CEUS allows depiction of microvasculization and the microvasculization between the lesion and the surrounding might be different [1, 6, 7, 10, 12, 13, 16, 18, 21-24, 27-30, 33, 34]. Some authors concluded that CEUS is useful for the differential diagnosis of benign and malignant polypoid lesions, whereas a recently released non-liver CEUS guideline was controversial [1,12,13,18,21,22,24,27,28,30,33,34]. In the guideline, the panel experts concluded that the differentiation between benign and malignant lesions is mainly determined by clinical features and size and enlargement of polyps to >10 mm is an indication for cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%